2019
DOI: 10.1177/1120672119881982
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and neurodegeneration in epilepsy

Abstract: Purpose: To compare optical coherence tomography measurements; central macular thickness, ganglion cell complex, and retinal nerve fiber layer thickness in patients with epilepsy versus healthy controls. Methods: We evaluated 28 eyes of 28 patients with epilepsy and 34 eyes of 34 healthy subjects. Central macular thickness, ganglion cell complex, and retinal nerve fiber layer thickness measurements were performed by spectral-domain optical coherence tomography. Results: Superior and superotemporal quadrant gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
(49 reference statements)
3
14
0
1
Order By: Relevance
“…Many prior studies also demonstrated thinner RNFLs and GCLs in patients with MS, both with and without a history of optic neuritis ( 58 , 59 ). Similarly, the association between thinner inner retinal layers and epilepsy has also been corroborated in previous small studies ( 60 , 61 ). Retinal OCT assessment has the potential to determine the presence and severity of atrophic cerebral changes previously only diagnosed and monitored using MRI brain scanning ( 62 ).…”
Section: Discussionsupporting
confidence: 82%
“…Many prior studies also demonstrated thinner RNFLs and GCLs in patients with MS, both with and without a history of optic neuritis ( 58 , 59 ). Similarly, the association between thinner inner retinal layers and epilepsy has also been corroborated in previous small studies ( 60 , 61 ). Retinal OCT assessment has the potential to determine the presence and severity of atrophic cerebral changes previously only diagnosed and monitored using MRI brain scanning ( 62 ).…”
Section: Discussionsupporting
confidence: 82%
“…A study by Bilen et al on the comparison of retinal thickness between healthy subjects and those with epilepsy showed significant thinning of this layer in patients, a different result than in the OCT images of the retinas of autistic children. This finding confirms generalized neurodegeneration in patients with epilepsy and may prove to be a useful tool for tracking and assessing neurodegenerative changes in ASD [ 44 ]. Ophthalmic symptoms regarding both fundus and retinal images from OCT examinations may precede the onset of neurological symptoms, further confirming the close correlation between the retina and the brain [ 55 ].…”
Section: Ophthalmic Manifestationssupporting
confidence: 64%
“…The retina, being an extension of the neurons of the central nervous system, is the outermost and most easily accessible layer of nerve cells used for the diagnosis of neuro-ophthalmic diseases. Currently, OCT examination is becoming a popular additional technique to help diagnose neurodegenerative diseases, i.e.,: multiple sclerosis, schizophrenia, Alzheimer’s disease, and Parkinson’s disease, where retinal differences in the macula and RNFL are found in the image of the second cranial nerve (retina nerve fiber layer—RNFL) disc [ 44 ]. OCT examination of the macula is a rarely described test used in children with ASD.…”
Section: Ophthalmic Manifestationsmentioning
confidence: 99%
“…Similarly, Bilen et al found a negative but not significant correlation between mean RNFL thickness and epilepsy duration. 29 Depending on the duration, it can be explained by the progression of neurodegenerative processes or the toxic effects of the cumulative doses of drugs on the retina.…”
Section: Discussionmentioning
confidence: 99%
“…They attributed this result to drug-resistant seizures and the duration of epilepsy. 29 Some studies reported that neurodegenerative diseases affected retinal ganglion cell axons, particularly those located in the macula. Reduction in macular volume has been reported in neurodegenerative diseases such as multiple sclerosis and Alzheimer's disease; however, this effect may also be due to drug-induced retinal toxicity.…”
Section: Discussionmentioning
confidence: 99%